Girls don't fly - Chandler, Kristen (Viking, 2011)
Myra, a high school senior, will do almost anything to win a contest and earn money for a study trip to the Galapagos Islands, which would mean getting away from her demanding family life in Utah and ex-boyfriend Erik, but Erik is set on winning the same contest.